Emphysematous Pancreatitis Mimicking Bowel Perforation. Issue 7 (20th July 2021) - Sandhu, Sunny; Alhankawi, Dhuha; Chintanaboina, Jayakrishna; Prajapati, Devang
ABSTRACT: Emphysematous pancreatitis is a rare complication of acute necrotizing pancreatitis, which carries a mortality rate of up to 70%. It has only been described in isolated case reports. We report a patient who presented with suspected bowel perforation and was subsequently found to have emphysematous pancreatitis that was managed successfully with multidisciplinary team involvement.